Keanekaragaman Jenis Lumut (Musci) di Lereng Gunung Wani, Suaka Margasatwa Buton Utara, Sulawesi Tenggara - Windadri, Florentina Indah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Diversity study on mosses at the slope of Wani mountain, North Buton Wild Life Reserve, South-east Sulawesi was conducted. There are 26 species belong to 14 genera and 8 families are recorded. Two genera i.e. Thuidium and Himanthocladium dominated in this area. Sixth species are recorded as â€œnew recordâ€ to Sulawesi i.e. Barbella pendula,Calyptotheciumcaudatum, Himantocladium plumula, Pinatella ambigua, Taxithelium alare, and Thuidium investe.